Evaluation of the efficacy of selective curettage in endodontic microsurgery - WANG Ke, YOU Jing, LU Wei (Editorial Office of Stomatology, 2024)
Objective To evaluate the efficacy of selective curettage when apical lesions are adjacent or involved to important structures in endodontic microsurgery (EMS). Methods A total of 264 patients who underwent EMS in the Department of Endodontics, The Affiliated Stomatological Hospital of Nanjing Medical University from January 2021 to January 2023 were selected as the research subjects. The cases of EMS were divided into selective curettage group (SC-EMS) and conventional curettage group (C-EMS). In SC-EMS group, patients with apical lesions involving or adjacent to important structures (mental foramen, mandibular neural tube, nasopalatine neural canal, maxillary sinus, nasal base and adjacent vital pulp teeth) were included, and the adjacent areas around important structures were selectively cureted. In C-EMS group, patients with apical lesions adjacent to important structures were treated with conventional apical curettage. The postoperative follow-up was 12 months, and the postoperative symptoms and imaging examinations of the patients were observed, and the efficacy was evaluated. The failure cases were examined after tooth extraction and preoperative pathological review to analyze the causes of failure. Results The success rate of SC-EMS group is 90.2%, and the success rate of C-EMS group is 95.4%. The rate of success in C-EMS group was higher, but there was no statistical difference between the two groups(P>0.05). Root fracture is the important causes for the failure of the two groups. There were 6 cases of short-term discomfort and 2 cases of long-term discomfort after SC-EMS. The C-EMS group didn't meet any short-term or long-term discomfort case. Conclusion Selective curettage has no significant effect on the success rate of EMS surgery, and is an effective method to protect important structures during surgery. Short-term discomfort may occur after surgery, and irreversible pulp damage of adjacent teeth occurs in a few cases.